2018
DOI: 10.2147/ott.s178916
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SOX18 in colorectal cancer cells promotes proliferation and correlates with colorectal cancer risk

Abstract: BackgroundSince colorectal cancer (CRC) is one of the most common malignant tumors worldwide, we aimed to identify the role of sex determining region Y (SRY)-box 18 (SOX18) in CRC.MethodsRT-PCR and immunohistochemistry were employed to detect the expression of SOX18 in CRC samples. We then identified the effect of SOX18 on cell proliferation, cell cycle, and apoptosis by cell counting kit-8 (CCK-8), flow cytometry, and annexin V/PI staining, respectively. The effect of silencing SOX18 expression in CRC develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…SOX18 is one of the members of the Sox subfamily, which has a crucial function in the formation of lymphatic network [ 22 ]. Using molecular, cellular, and genetic assays, SOX18 is shown to be important for the differentiation of lymphatic endothelial cells in mice [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOX18 is one of the members of the Sox subfamily, which has a crucial function in the formation of lymphatic network [ 22 ]. Using molecular, cellular, and genetic assays, SOX18 is shown to be important for the differentiation of lymphatic endothelial cells in mice [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOX18 is one of the members of the SOX subfamily, which plays an important role in cell differentiation and cell survival during embryonic development [ 21 ]. SOX18 has a crucial function in the formation of lymphatic network [ 22 ]. It has been demonstrated that SOX18 promotes lymphatic vessel formation in both embryogenesis and tumor-induced lymphangiogenesis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…VEGFD can induce both intra-and peri-tumoral lymphatic vessel development; however, it is not involved in lymph node metastasis [29]. Finally, a series of lymphatic factors, including PROX1, VEGFC, PDPN, VEGFR-3, SOX18 (SRY-Box transcription factor 18), and COUP-TFII (Nuclear receptor subfamily 2 group F member 2) can be expressed in tumoral cells and, consequently, control their properties, such as invasion, migration, proliferation, survival, epithelial to mesenchymal transition (EMT), and adhesion [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Sex-determining region Y-box 18 (SOX18) is a member of the sex-determining region of the Y-chromosome-related high-mobility group box (SOX) family of transcription factor. There are some studies have reported that SOX18 functioned as an oncogene in tumors by regulating cell cycle and apoptosis [ 42 ā€“ 44 ]. However, its molecule mechanism in osteosarcoma has not yet been discovered [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%